IDENTIFICATION OF FACTORS FOR INCEPTION OF SLUMS: USING GRAVITATIONAL MODEL (International Journal of Engineering Sciences & Management Research, 2018)
Today, the problem of slums is increasing throughout the world especially in developing countries like India. Slum communities are usually inhabited by socially disadvantaged people. It is more common in developing countries. It can be defined by poverty, low income, inadequate living conditions and sub-standard facilities. The condition of slum varies from place to place and country to country. Since each slum is being formed in different ways slum dwellers are experiencing different hardships according to different socio-economic environments. The study is focused on the location of inception of slums, and its factors responsible for slum development. In this study, the factors responsible for the development of slums have been found out, which attract the people for making slum on a piece of land are analysed.